Investigating the causal effect of various metabolites on postherpetic neuralgia: a Mendelian randomization study - Zhu, Jianyu; Chen, Jiahao; Zuo, Yuefen; Song, Kun; Liao, Huilian; Wu, Xianping (Frontiers in Neurology, 2024)
BackgroundCommon side effect of Herpes Zoster, postherpetic neuralgia (PHN), causes persistent pain that seriously affects quality of life. Lack of dependable biomarkers makes the clinical diagnosis and treatment of PHN difficult, so complicating the assessment of therapeutic efficacy. Blood metabolites are becoming more and more well known as significant disease markers. With an aim to find possible biomarkers for diagnosis and treatment, this work investigates the causal link between blood metabolites and PHN using Mendelian randomization.MethodsThis work evaluated causal relationships between PHN and 1,091 plasma metabolites using Mendelian randomization (MR). Complementing MR-Egger and weighted median approaches, the main causality analysis was done using inverse variance weighted (IVW) and Wald ratio (WR) approaches. Robustness was checked using sensitivity analyses including CAUSE, Cochran’s Q tests, leave-one-out analysis, MR-PRESSO, and MR-Egger intercept analysis. Reverse MR analysis and linkage disequilibrium score regression (LDSC) was used to assess significant correlations as well. Two-step MR analysis was also used to look at the mediating function of positively correlated metabolites in the causal pathway.ResultsThe results of this study indicated a significant association between N-acetyl-aspartyl-glutamate (NAAG) and PHN, with an odds ratio (OR) of 0.83 (95% CI: 0.76–0.91, p = 2.68E-05). Moreover, five potential associated metabolites were identified: Gamma-glutamylthreonine (OR = 1.60, 95% CI: 1.16–2.20, p = 0.004), 3-hydroxyphenylacetoylglutamine (OR = 1.43, 95% CI: 1.00–2.05, p = 0.048), Caprate (10:0) (OR = 1.86, 95% CI: 1.11–3.12, p = 0.018), X-12013 (OR = 1.64, 95% CI: 1.03–2.60, p = 0.035), and X-17328 (OR = 1.50, 95% CI: 1.04–2.18, p = 0.032). Additionally, NAAG likely acts as a complete mediator between FOLH1(CGPII) and postherpetic neuralgia in the causal pathway.ConclusionThe results of this study indicated a significant association between N-acetyl-aspartyl-glutamate (NAAG) and PHN, with an odds ratio (OR) of 0.83 (95% CI: 0.76–0.91, p = 2.68E-05). Furthermore five possible related metabolites were found: Glutamylthreonine gamma-wise (OR = 1.60, 95% CI: 1.16–2.20, p = 0.004), 3-hydroxyphenylacetoylglutamine (OR = 1.43, 95% CI: 1.00–2.05, p = 0.048), Caprate (10:0) (OR = 1.86, 95% CI: 1.11–3.12, p = 0.018), X-12013 (OR = 1.64, 95% CI: 1.03–2.60, p = 0.035), and X-17328 (OR = 1.50, 95% CI: 1.04–2.18, p = 0.032). Furthermore, in the causal pathway NAAG most certainly serves as a complete mediator between FOLH1(CGPII) and postherpetic neuralgia.